Synthesis, characterization and electrochemical properties of cadmium sulfide – Reduced graphene oxide nanocomposites - Sagadevan, Suresh; Chowdhury, Zaira Zaman; Johan, Mohd Rafie; Aziz, Fauziah Abdul; Roselin, L. Selva; Hsu, Hsiu Ling; Selvin, Rosilda (Elsevier, 2019)
Nowadays, research interest is speedily growing for fabrication of semiconductor metal sulfide nanoparticles. Proper optimization of process variables for the synthesis process can ensure tunable morphologies and distinct characteristics. Appropriate synthesis strategy can alter their electrical, optical and catalytic properties significantly. A simple, one step, the hydrothermal approach has been undertaken to prepare CdS/rGO nanocomposite here. This technique ensures fabrication of graphene-based nanocomposites with outstanding electro-catalytic characteristics using a facile route. The structural, morphological and the electrochemical properties of the synthesized sample were observed. Surface morphological features together with its phase was identified using FESEM, TEM, and XRD analysis. The crystalline phase of the synthesized sample was confirmed from the X-ray diffraction pattern. Surface functional groups of the synthesized sample were analyzed using the FTIR and FT-Raman analysis. The optical characterization of the CdS and CdS/rGO nanocomposite were examined. The FESEM and TEM images were used to illustrate the surface morphology and particle size of the CdS and CdS/rGO nanocomposite. The elemental composition of the synthesized sample was evaluated using EDAX analysis. In this research, the values for dielectric loss, dielectric constant, and resistivity and AC conductivity of the synthesized samples were determined. Thus, the overall electrochemical features of the prepared sample were evaluated. The results elucidated here showed that the synthesized sample can be used as potential electrode materials for supercapacitor ensuring high energy.